ANALISIS KEARIFAN LOKAL BUDAYA TUTUR LISAN SEBAGAI PEREKAT KEBANGSAAN DAN HARMONISASI SOSIAL MASYARAKAT KALIMANTAN TIMUR - Ahmad Jubaidi (Prodi Ilmu Administrasi Negara, 2021)
The purpose of this research is to analyze the existence and role of local wisdom of oral speech culture as the social glue and social harmonization of the people of East Kalimantan. Local wisdom is one of the instruments to reduce or minimize the problems of social conflict, intolerance, radicalism and other forms of violence. One form or form of local wisdom is the local wisdom of oral speech culture as the national glue that has been passed down by our ancestors, the nation's founders as one of the norms, customs and principles in stepping to create calm, peace, glue and harmony in social life and patriotic.The focus of the research, namely: the name of the Local Wisdom of the Oral Culture), the Textual Definition of the local wisdom, the History / Origin of the local wisdom, the description of the implementation of local wisdom in the daily behavior of the community, the Moral Values that are owned / contained from the local wisdom, Evidence in the form of Documents / Photos Portraits as illustrations in life, and the current condition of local wisdom, is it still Live or Live out in the life of the community.The results show the local wisdom of oral speech culture, namely the words of King Senduru when he was crowned the King of Nature can be seen in the Collection of Folk Stories in Kutai, Pemda Kabupaten Kutai, 1977). Moral Value Contained in local wisdom in making decisions should always prioritize deliberation, no one will feel defeated so as to avoid resentment and resentment. Hate and revenge can give birth to the desire to avenge their defeat and this is very bad for the Indonesian people who always prioritize harmony, harmony and unity.Local wisdom is the curse of the Kudungga king. The moral values contained in it are corruption and illegal plunder of the earth since ancient times have been strictly prohibited. So that those who do not heed the curse will have an impact on him either directly or gradually. The local wisdom is still valid today.Local wisdom, said Buen Kesong (Good Heart) from the Paser tribe in Paser Regency, is a source of common strength to harmonize steps in establishing a relationship together. It even illustrates the mystical atmosphere of the people of Paser Regency who have a clean heart in thinking and working,